2017
DOI: 10.1177/1010428317725442
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin-c isoform levels are associated with SR and hnRNP differential expression in ovarian cancer cell lines

Abstract: Osteopontin-c splicing isoform activates ovarian cancer progression features. Imbalanced expression of splicing factors from serine/arginine -rich and heterogeneous ribonucleoproteins families has been correlated with the generation of oncogenic splicing isoforms. Our goal was to investigate whether there is any association between the transcriptional patterns of these splicing factors in ovarian cells and osteopontin-c expression levels. We also aimed to investigate the occurrence of these splicing factors bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…OC was the result of the interaction of multiple genetic and environmental factors, many reports showed that multiples genes may be involved in the pathogenesis of this disease [12][13][14]. However, these genes were mainly nuclear genes; little was known the role of mitochondrial dysfunction in OC.…”
Section: Discussionmentioning
confidence: 99%
“…OC was the result of the interaction of multiple genetic and environmental factors, many reports showed that multiples genes may be involved in the pathogenesis of this disease [12][13][14]. However, these genes were mainly nuclear genes; little was known the role of mitochondrial dysfunction in OC.…”
Section: Discussionmentioning
confidence: 99%
“…OPN primary transcript is subject to alternative splicing and, in addition to other post-transcriptional and post-translational OPN variants, total OPN (the sum of all OPN variants, which we named herein as OPN) has been widely studied in cancer cells [ 27 ]. Among OPN splice variants, Osteopontin-c (OPN-c) splicing isoform seems to activate OC progression features [ 28 ]. The role of OPN and OPN-c in OC has been intensively studied in two recent published meta-analyses [ 29 , 30 ], indicating that it may be a potential diagnostic and prognostic biomarker.…”
Section: Introductionmentioning
confidence: 99%